KEBERLANJUTAN PARIWISATA BERBASIS ALAM : UKURAN BUDAYA DAN PERILAKU KEPRIBADIAN - Ali Imron; Rizka Ariyanti; Nur Rokhman (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
This study aims to justify the relevance of tourism destination culture personality (TDCP) for measuring destination personality from a cultural measures and personality behaviour perspective. Employing the cultural measures and personality behaviour approach, the study examines how TDCP can strengthen tourist engagement and memorable experiences, leading to higher revisit intentions, particularly when the destination image aligns with tourists' self-concept. TDCP integrates destination personality and Hofstede's cultural dimensions to define a destination's unique cultural identity. The study performs quantitative research method and involved 259 respondents from a single nation to evaluate 15 scale items of TDCP. SEM-AMOS and IPMA statistical analyses are performed to confirmed TDCP's measurement item and the role. We found TDCP has significance in optimising the relationship between tourist engagement, memorable experiences, and revisit intention. Additionally, TDCP demonstrated a È-shaped curvilinear relationship with tourist engagement and revisit intention. Robustness and configuration tests validated the findings. This study contributes to tourism literature by detailing the impact of TDCP dimensions on tourist engagement, memorable experiences, and revisit intention in NBT. Keywords: tourism destination culture personality, tourist engagement, memorable-based tourism experience, revisit intention, Hofstede’s dimension of cultural, destination personality, tourism sustainability.